Operational Efficiency and Accuracy in Forecasting Drug Demand: The Application of Technology in Stock Management - Giovanni, Rabibisoa; Sukmawaty, Sukmawaty; Lewa, Inriati; Indarwati, Indarwati (JURNAL PROTEKSI KESEHATAN, 2024)
Despite the critical role of medicine stock management in ensuring drug availability in health facilities, existing practices often suffer from inefficiencies and inaccuracies, particularly in predicting drug demand. This study addresses these gaps by integrating information technology (IT) into medicine stock management, examining its impact on operational efficiency and predictive accuracy. Employing a mixed-methods approach, data were collected from surveys, interviews, and case studies across various healthcare facilities and analyzed using the MERISE methodology. Findings reveal that IT implementation significantly enhances efficiency, reduces human errors, and improves decision-making speed. Furthermore, capacity building for stock management staff is crucial in sustaining performance improvements. The study underscores the necessity of robust policies and cross-sector coordination to optimize stock management. Its contribution lies in offering a practical framework for IT-driven stock management, with broader implications for global healthcare efficiency, ensuring accurate medicine availability, and improving service quality in diverse health settings.